Produção, circulação e funcionamento da censura na ditadura militar brasileira e no fascismo italiano : a censura no ordem do discurso - Moreira, Carla Barbosa (2009)
This thesis, based on the French discourse analysis framework that considers the historic determination of meaning process, aimed at analyzing the discourse order of censorship considering the social historic practices produced in the language. It tried to understand an ideological order responsible for the production, legitimating and on going of censorship during the Brazilian military dictatorship and Italian fascism period. It was possible to get to similar censorship knowledge through the analysis of documents of different censorship archives. In this sense, despite the fact that the analyzed discourses censured journalistic, published journalistic, censorship rules, official dictatorship documents and censor books formation had been done in periods in which the institutionalized censorship had been predominant, the analysis about them also allowed to understand that the way how the meaning is produced in the whole discourse depends on the force relation between the ideological formations, relations that intend to control the meanings, but also resist to others. In this thesis, the censorship, in a more or less incisive manner, is understood as a force that constitute itself in the discourse processes to control what can and must be said, what can not or must not be said, considering that it is in the discourse that the sayings and meanings in conflicts are produced. It is a conflict that always presents censorship and resistance in a relationship represented by repetition, persistence and insistence in how to resist to the control and silencing of meanings.